Sexual and reproductive health of women living with HIV in Muslim-majority countries: a systematic mixed studies review - Dyah Juliastuti; Judith Dean; Lisa Fitzgerald (BMC, 2020)
Abstract Background The number of women living with the human immunodeficiency virus (WLHIV) in Muslim-majority countries has increased significantly in the last decade. These women are often marginalized and face insecure sexual and reproductive health (SRH) needs and rights. However, little is known about the multi-faceted factors influencing these women's fertility, contraceptive, and perinatal decisions and sexual life. This systematic mixed studies review aimed to synthesize the empirical evidence on social, cultural, and structural factors influencing the SRH of WLHIV in Muslim-majority countries. Methods This review provides a synthesis of quantitative, qualitative and mixed-method research findings searched from PubMed, EMBASE, Scopus, CINAHL and Cochrane databases. We screened 3452 SRH studies involving WLHIV. The studies, published in English between 2008 and 2017, were from 20 Muslim-majority countries with increased numbers of WLHIV. The quality of eligible studies was appraised using a mixed-methods appraisal tool (MMAT) version 2011. Findings were thematically analysed by a hybrid deductive-inductive approach. Two independent reviewers were involved in the study selection, data extraction, quality appraisal, and data synthesis. Results We included 13 SRH-related studies involving 1748 WLHIV in eight Muslim-majority countries. Most of these studies explored fertility desire and sexual health, while only a small proportion related to contraceptive use and the perinatal-care experience. We identified that WLHIV faced neglect of their SRH rights. These rights were predominantly affected by the socio-cultural, religious and health-services context of the women's lives, which directed them to unsafe sex practices and stressful perinatal experiences. Conclusions This study points to the need for SRH laws, policies, and interventions which stop WLHIV experiencing SRH discrimination violence and achieving their SRH rights.